Field Evaluation of Container Nursery Irrigation Systems: Measuring Uniformity of Water Application of Microirrigation Systems: FS981/AE193, 6/2001 - Haman, Dorota Z.; Yeager, Thomas H. (EDIS, 2001)
Performance of microirrigation systems can be evaluated by measuring operating pressures, application rates, and uniformity of water application under nursery conditions. This document presents a simple test to determine the uniformity of water application.